Efeitos da adição de resíduos de cinza da casca de café na microestrutura e propriedades de cerâmicas à base de cordierita - Ferreira, Pedro Alighiery Silva de Araújo (2021)
Cordierite is one of the compounds of the MgO-Al2O3-SiO2 system that presents the lowest thermal expansion coefficient among the inorganic oxides. Despite this advantage, which results in high thermal shock resistance, monophasic cordierite is difficult to prepare due to its narrow sintering range and the existence of secondary phases that raises its thermal expansion coefficient. Fluxes are generally used to stimulate the sintering of cordierite precursor powders and to modify the microstructures and properties of these ceramics. In this context, this paper proposes to study the effects of adding different levels of Coffee Husk Ash Residue (CHAR), as fluxing agent, on the elimination of secondary phases, analyzing the behavior during sintering processes and the effects on the microstructures obtained and the properties of cordierite-based ceramics. A standard formulation was prepared using kaolinitic clay, talc and alumina as a source of the elements: aluminum, silicon and magnesium. Samples of the pure standard formulation and of the formulation containing different content of CHAR were prepared by reactive sintering (in conventional kiln) in the temperature range between 1250 and 1450 °C. The quantitative phase analysis of sintered samples was determined by Rietveld refinement of XRD (X-Ray Diffraction) data. Physical properties were estimated by Archimedes methodology, microstructure was inspected by Scanning Electron Microscopy (SEM). The coefficient of thermal expansion was determined using a thermal dilatometer and the dielectric properties were determined by impedance spectroscopy. The addition of up to 1% of CHAR stimulated the reaction between cristobalite and spinel to form cordierite, contributing to the decrease of apparent density and increase of apparent porosity, but with the addition of more than 1% of CHAR, the content of the cordierite phase reduces and there is an increase of spinel in nearly the same proportion, contributing to the increase of the thermal expansion coefficient. The samples with 2% and 4% of CHAR content by weight presented an unprecedented discontinuity of electrical behavior for aluminosilicate based materials.